Comprehensive analysis of protective effects of Loranthus tanakae Franch. and Sav. on ovalbumin-induced atopic dermatitis in mice and TNF-α/INF-γ-stimulated HaCaT cells - Yea-Gin Yang; Woong-Il Kim; A. Yeong Lee; So-Won Pak; Sin-Hyang Park; Young-Kwon Cho; Joong-Sun Kim; Jong-Choon Kim; Sung-Hwan Kim; In-Sik Shin (Animal Cells and Systems)
Loranthus tanakae Franch. and Sav. is a traditional herbal remedy with anti-inflammatory and antioxidative properties, used to treat joint and respiratory inflammation. In this study, we investigated the therapeutic effects of L. tanakae ethanol extract (LTE) on atopic dermatitis (AD). An ovalbumin (OVA)-induced AD animal model and a human keratinocyte cell line, HaCaT, were used to assess LTE treatment effects on AD. An in vitro experiment showed that LTE treatment significantly decreased the production of regulated upon activation, normal T cell expressed and secreted (RANTES) cytokines and macrophage-derived chemokines (MDC) in tumor necrosis factor-alpha (TNF-α)/interferon-gamma (IFN-γ) (TNF-α/IFN-γ)-stimulated HaCaT cells in a concentration-dependent manner. In addition, treatment with LTE markedly reduced the translocation of signal transducer and activator transcription 1 (STAT1) protein to the nucleus and the phosphorylation of Janus kinase 2 (JAK2) in TNF-α/IFN-γ-stimulated HaCaT cells. In the in vivo experiment, administration of LTE significantly decreased the levels of immunoglobulin E (IgE) and interleukin-13 (IL-13) of OVA-induced AD mice, which was supported by histological evidence. Moreover, LTE treatment markedly reduced inflammatory cell infiltration and edema in the OVA-induced AD mice’s damaged lesions. In addition, applying LTE notably inhibited the phosphorylation of JAK2 and STAT1 in the OVA-induced AD mice, supported by in vitro results. In conclusion, LTE effectively alleviated the AD-induced skin inflammation in the OVA-induced AD animal model and TNF-α/IFN-γ-stimulated HaCaT cells; this was related to the suppression of JAK2 and STAT1 phosphorylation. These findings suggest that LTE has potential as a therapeutic agent for AD management.